2009
DOI: 10.1590/s1516-89132009000300024
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Nile tilapia Oreochromis niloticus fed diets with different levels of proteins of yeast

Abstract: This experiment was based on observations of 72 juveniles of Nile tilapia (Oreochromis niloticus)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The process of cooking decreases redness and increases lightness and yellowness (Cofrades et al., 2011) by enhancing white coloration. Consumers regard white meat as one of the most important qualities of tilapia (Medri et al., 2009). Our results showed that the 50% KCl treatment (T1) intensifies this feature.…”
Section: Resultsmentioning
confidence: 99%
“…The process of cooking decreases redness and increases lightness and yellowness (Cofrades et al., 2011) by enhancing white coloration. Consumers regard white meat as one of the most important qualities of tilapia (Medri et al., 2009). Our results showed that the 50% KCl treatment (T1) intensifies this feature.…”
Section: Resultsmentioning
confidence: 99%
“…Although differences in the measured color values of cooked restructured tilapia steaks were observed, our data demonstrate that the addition of MTG did not negatively affect the lightness of the MTG-treated product. Additionally, light color is one of the most important visual traits of tilapia product perceived by consumers (Medri et al 2009). Therefore, the results indicate the application potential of these MTG concentrations in restructured tilapia steaks.…”
Section: Cooked Restructured Tilapia Steaksmentioning
confidence: 99%
“…Nile tilapia (Oreochromis niloticus) is a tropical climate fish of considerable rusticity for cultivation, with a delicate flavor, and a good quality of nutritional aspects with low fat content and free of Yshaped bones (Medri et al, 2009). For these characteristics this is one of the most cultivated species in the world.…”
Section: Introductionmentioning
confidence: 99%